Influence of soil water content and atmospheric conditions on leaf water potential in cv. "Touriga Nacional" deep-rooted vineyards - Rodrigues, P. (2012)
Abstract In this study, the influence of soil and atmosphere conditions on noon and basal leaf water potential of vines ‘‘Touriga Nacional’’ in the Da˜o region submitted to different irrigation treatments is analysed. Both indicators showed to be dependent on environmental conditions at the time of measurement. Leaf water potential at noon of fully watered plants was linearly related with atmospheric conditions, with values registered when vapour pressure deficit (VPD) was higher than approximately 3 kPa being no different from the values registered in stressed plants. Therefore, this indicator cannot be reliably used to distinguish different plant water stress levels when atmospheric conditions induce high evaporative demands. The basal leaf water potential (wb) was also influenced by VPD at the time of measurement for all soil water conditions. In well irrigated plants, it was even possible to establish a baseline that can therefore be used to identify nonwater stressed conditions (wb (MPa) = -0.062–0.0972 VPD (kPa), r2 = 0.78). A good correlation was found between soil humidity and wb. However, more than the average value of the whole thickness of soil monitored, the wb values were dependent on the distribution of soil humidity, with the plants responding to the presence of wet layers.